Place-based instruction in archives: our pedagogical roots. Issue 1 (January 2020) - Schwier, Carrie; Champion, Carey
Abstract : Archival instruction has undergone an evolution of growth over the past several years. As archivists at colleges and universities increase their instructional roles, it is to the benefit of students and instructional partners that archivists inform themselves of relevant learning theories that can influence teaching with campus heritage collections. Place-Based Education (PBE) leverages local environments, communities, resources and people into immersive learning opportunities. It prioritizes engagement and authentic interactions and offers instructional archivists the opportunity to harness the power of place inside the classroom. This article provides an overview of the pedagogical landscape in archives, an introduction to place-based teaching and learning and case studies from courses at Indiana University.